Management Mistakes and Successes, Tenth Edition - Hartley, Robert (John Wiley & Sons, 2010)
Hartley's casebook is rich in content with easy to read case studies that are well suited for business professionals. They'll learn every key aspect of management, from performance and crisises; to mergers and acquisitions. The tenth edition presents more new case studies to illustrate management concepts. These include Google's entrepreneurial strategy, Procter and Gamble, Starbucks, and more. Recent business failures and successes are also examined in a way that offers practical insights and strategic principles. By focusing on the mistakes and successes, this book helps business professionals learn how to become great business leaders.